Microglial polarization and plasticity: Evidence from organotypic hippocampal slice cultures. Issue 10 (5th August 2013) - Antonietta Ajmone‐Cat, Maria; Mancini, Melissa; De Simone, Roberta; Cilli, Piera; Minghetti, Luisa
Abstract : Increasing evidence indicates that "functional plasticity" is not solely a neuronal attribute but a hallmark of microglial cells, the main brain resident macrophage population. Far from being a univocal phenomenon, microglial activation can originate a plethora of functional phenotypes, encompassing the classic M1 proinflammatory and the alternative M2 anti‐inflammatory phenotypes. This concept overturns the popular view of microglial activation as a synonym of neurotoxicity and neurogenesis failure in brain disorders. The characterization of the alternative programs is a matter of intense investigation, but still scarce information is available on the course of microglial activation, on the reversibility of the different commitments and on the capability of preserving molecular memory of previous priming stimuli. By using organotypic hippocampal slice cultures as a model, we developed paradigms of stimulation aimed at shedding light on some of these aspects. We show that persistent stimulation of TLR4 signaling promotes an anti‐inflammatory response and microglial polarization toward M2‐like phenotype. Moreover, acute and chronic preconditioning regimens permanently affect the capability to respond to a later challenge, suggesting the onset of mechanisms of molecular memory. Similar phenomena could occur in the intact brain and differently affect the vulnerability of mature and newborn neurons to noxious signals. GLIA 2013;61:1698–1711